Three team and organisational culture myths and their consequences for sport psychology research and practice - McDougall, M.; Ronkainen, N.; Richardson, D.; Littlewood, M.; Nesti, M. (International Review of Sport and Exercise Psychology, 2020)
In this article, three prevailing myths about team and organisational culture - an increasingly popular topic in applied sport psychology research and practice - are identified, reviewed and challenged. These are; that culture is characterised only by what is shared, that culture is a variable and therefore something that a particular group has, and that culture change involves moving from the old culture to an entirely new one. We present a challenge to each myth through the introduction of alternative theoretical and empirical material and discuss the implications for sport psychology research and practice. The intent of this endeavour is to stimulate debate on how to best conceptualise and study culture. More broadly, we aim to encourage sport psychologists to consider team and organisational culture in new and/or varied ways, beyond current conceptualisations of consensus, clarity, integration and as a management tool to facilitate operational excellence and on-field athletic success.